Removal of fluoride and arsenic from groundwater by hybrid Al–Fe electrocoagulation: Adsorption isotherm and kinetics study of single and binary component systems. Issue 4 (16th March 2021) - Nyangi, Magori J.; Chebude, Yonas; Kilulya, Kessy F.; Minu, Andrew
Abstract: This study reports on the adsorption isotherm and kinetics of arsenic and/or fluoride by the hybrid iron–aluminum electrocoagulation in a batch reactor. The experiments were performed at a condition of current density J = 9.9 mAcm −2 ; time = 50 min; and pH = 7.5, at variable initial concentrations. The flocs surfaces were characterized using Fourier transform infrared spectroscopy and X‐ray powder diffraction that revealed presence of AlAsO4 ·2(H2 O), AlF2 OH, and FeOOAs. Adsorption of fluoride and arsenic in both systems followed Freundlich and Langmuir models. The adsorption processes for fluoride and arsenic were spontaneous and physical in nature with monolayer maximum adsorption capacities of 76.4 and 1.14 mg/g, respectively in single systems. In a binary component system, the adsorption capacity of arsenic was 0.06 mg/g while that of fluoride became 75.6 mg/g as evaluated using extended Langmuir and extended Freundlich models. Moreover, the kinetics of fluoride and/or arsenic adsorption followed the pseudo second‐order model. The remediation of fluoride and arsenic from water by Al–Fe oxyhydroxide were found to be through ionic exchange and electrostatic attraction, respectively.